Design and Implementation of a LoRa Adaptive Rate Algorithm Based on Power Optimization - Wang, Honggang; Chen, Hao; Lu, Junyan; Zhang, Bohan; Pang, Shengli; Pan, Ruoyu (2023 International Conference on Networks, Communications and Intelligent Computing (NCIC), 2023)
With the increasing popularity of LoRa technology in the Internet of Things (IoT) field, many devices are being added to LoRa networks, increasing the complexity and randomness of the networks. Interference and obstacles such as object blocking, electromagnetic interference, and multipath propagation may affect communication in complex environments, leading to degraded signal quality, reduced coverage, and shorter communication distances. In order to address these issues, this paper proposes an adaptive rate algorithm based on the LoRa channel quality indicator and energy consumption level. This algorithm utilizes the predicted LoRa channel quality and evaluates the energy consumption of LoRa devices to dynamically adjust the transmission rate, adapting to changes in the network environment and achieving optimal communication performance. Experimental results show that the proposed algorithm has high adaptability and robustness in complex environments, effectively improving the stability and reliability of LoRa communication, and it has superior energy consumption performance. Compared to the standard ADR and ADR+ algorithms, the proposed algorithm exhibits more stable single and multi-terminal data packet transfer success rates in a LoRa network, with relatively lower energy consumption.